Pendampingan Legalitas Usaha melalui Penerbitan NIB dan Sertifikasi Halal Sebagai Upaya Peningkatan Kepatuhan UMKM di Dukuh Sutorejo - Bayu Setiawan Priambodo; Endang Iryanti (Universitas Pahlawan Tuanku Tambusai, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the community’s economy; however, many business actors still lack adequate business legality. This condition is also found among MSMEs in Dukuh Sutorejo. This community service activity aims to implement business legality assistance through the issuance of a Business Identification Number (NIB) and the submission of halal certification as an effort to improve MSME compliance. The method employed is participatory assistance carried out through socialization, technical assistance, and monitoring and evaluation. The results indicate that the assistance activities improved MSMEs’ understanding of the importance of business legality and facilitated the process of obtaining NIB and halal certification. With proper business legality, MSMEs are better prepared to operate formally and sustainably.